Islam and The Plight of Internally Displaced Persons (IDPS) In IDP Camps in Abuja, Nigeria - Seleiman B Mohammad; Rafatu Abdulhamid (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2021)
The paper is based on a study conducted on the Plight of Internally Displaced Persons (IDPs) in Abuja, Federal Capital Territory, Nigeria. The study sought to find out the socio-economic and psychological conditions of three IDP camps in Durumi, Karmajiji and Dakwa, and the extent of state and non-state actors support to the camps. Data was sourced through key Informant Interview, Focus Group Discussion and documents. The IDPs lacked access to quality hygiene, education and health services and found to be distressed and traumatized. The study found little support from the state, but enormous contributions from NGOs and philanthropists. The study recommends among others that IDP camps should be taken over by the state to provide basic amenities and empowerment